Saberes tradicionais e o ensino de Ciências : um estudo de caso na comunidade ribeirinha Nossa Senhora Aparecida do Miriti - Parintins/AM - Brandão, Gelciane da Silva (2019)
The dissertation "Traditional Knowledge and Teaching of Sciences: a case study in the riverside community Nossa Senhora Aparecida do Miriti – Parintins/AM" was produced from a phenomenological description, in order to emerge as a device of alterity between canonical knowledge and the traditional. In the riverside community N. Sra. Aparecida do Miriti, with five social agents (BOURDIEI, 2008), we perform the ethnographic description of the place and its historiography, we identify the emic categories: panema, quebranto, reima, and the belief system and myths. The objective was to understand the possibility of articulating the traditional knowledge to the teaching of Sciences, considering the perception of the social agents in relation to water, land and forest in the cited community. The procedures adopted went through the production of the history of the community through the production of a collective sketch; a survey of the genesis of traditional knowledge of water, land and forest, of the emic categories that the social agents manifested in relation to traditional knowledge and their relations to Western science. It was a qualitative research (CRESWELL, 2010), with a phenomenological procedure (MERLEAU-PONTY, 199) based on a case study. As techniques, we conducted interviews, free and participant observation, production of written and oral artifacts guided by ethnographic elements (MALINOWKI, 1884-1942), as well as a problematization of knowledge, (Foucault, 2008; Almeida, 2008 and Levi-Strauss 1989 ); of the traditional term (HOBSBAWM, 19997; THOMPSON, 1998 and ALMEIDA, 2008b); as well as discussions about traditional knowledge (PONTES FILHO, 2016; ALMEIDA, 2008); community (BAUMAN, 2003; HARRIS, 2006); (SOUZA, 2013) and Teaching of Sciences (DELIZOICO, ANGOTTI and PERNAMBUCO, 2011). We conclude that there is a possibility of articulating the traditional knowledge to the teaching of science from the discipline of geography, focusing on concepts in the categories landscape and place, and that traditional knowledge and Westernized science must dialogue, so that they can demonstrate that life precedes consciousness and that the lived world resists being deconstituted by Western reason. Keywords: Knowledge, Traditional, Community, Phenomenology, Science Teaching.